Pulmonary rehabilitation coupled with negative pressure ventilation decreases decline in lung function, hospitalizations, and medical cost in COPD: A 5-year study. Issue 41 (October 2016) - Huang, Hung-Yu; Chou, Pai-Chien; Joa, Wen-Ching; Chen, Li-Fei; Sheng, Te-Fang; Lin, Horng-Chyuan; Yang, Lan-Yan; Pan, Yu-Bin; Chung, Fu-Tsai; Wang, Chun-Hua; Kuo, Han-Pin
Abstract : Abstract: Pulmonary rehabilitation (PR) brings benefits to patients with chronic obstructive pulmonary disease (COPD). Negative pressure ventilation (NPV) increases ventilation and decreases hyperinflation as well as breathing work in COPD. We evaluated the long-term effects of a hospital-based PR program coupled with NPV support in patients with COPD on clinical outcomes. One hundred twenty-nine patients with COPD were followed up for more than 5 years, with the NPV group (n = 63) receiving the support of NPV (20–30 cm H2 O delivery pressure for 60 min) and unsupervised home exercise program of 20 to 30 min daily walk, while the control group (n = 6) only received unsupervised home exercise program. Pulmonary function tests and 6 min walk tests (6MWT) were performed every 3 to 6 months. Emergency room (ER) visits and hospitalization with medical costs were recorded. A significant time-by-group interaction in the yearly decline of forced expiratory volume in 1 s in the control group analyzed by mixed-model repeated-measure analysis was found ( P = 0.048). The 6MWT distance of the NPV group was significantly increased during the first 4 years, with the interaction of time and group ( P = 0.003), the time alone ( P = 0.014), and the quadratic time ( P  < 0.001) being significant between the 2 groups. ER exacerbations and hospitalizations decreased by 66% ( P  < 0.0001) and 54% ( P  < 0.0001) in the NPV group, respectively. Patients on PR program coupled with NPV had a significant reduction of annual medical costs ( P = 0.022). Our hospital-based multidisciplinary PR coupled with NPV reduced yearly decline of lung function, exacerbations, and hospitalization rates, and improved walking distance and medical costs in patients with COPD during a 5-year observation Abstract : Supplemental Digital Content is available in the text